Perlindungan Hukum Terhadap Pihak Ketiga Sebagai Pemilik Alat Berat Yang Digunakan Dalam Melakukan Tindak Pidana Perambahan Hutan - Erlita Sipayung; Kartina Pakpahan; Heni Widiyani; Nelly Sri Devi (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2019)
Abstract Forests are the lungs of the earth that produce huge amounts of oxygen that humans need to live. But at this time there are many criminal acts of forest encroachment that are carried out irresponsibly, so that it harms many parties such as third parties as owners of heavy equipment used to commit acts of forest encroachment. Article 78 paragraph (15) of Law Number 41 of 1999 concerning Forestry which stipulates that all forest products and proceeds of crime, violations or transportation equipment used to commit crimes or violations will be confiscated for the State. From this article, injustice arises for third parties who have heavy equipment when renting to others because their heavy equipment is seized by the State. Because the third party only rents the heavy equipment to other people without knowing that the person who hired uses it for a crime. This study uses a normative juridical method with library research data collection techniques, qualitative data analysis using inductive deductive methods. The legal action that can be taken by a third party is to object to the seizure placed on the object or object belonging to a third party as long as the case against it has not yet had a decision that has permanent legal force. By taking legal action against third parties to recover their property that was confiscated based on a decision concerning evidence of a crime which was considered relevant enough to provide justice to a third party.